Identification of N‐arachidonoyl dopamine as a highly biased ligand at cannabinoid CB1 receptors. (17th November 2015) - Redmond, William J.; Cawston, Erin E.; Grimsey, Natasha L.; Stuart, Jordyn; Edington, Amelia R.; Glass, Michelle; Connor, Mark
Abstract : Background and Purpose: N ‐arachidonyl dopamine (NADA) has been identified as a putative endocannabinoid, but there is little information about which signalling pathways it activates. The purpose of this study was to identify the signalling pathways activated by NADA in vitro . Experimental Approach: Human or rat cannabinoid CB1 receptors were expressed in AtT20, CHO or HEK 293 cells. NADA displacement of radiolabelled cannabinoids, and CB1 receptor mediated activation of K channels or ERK phosphorylation, release of intracellular calcium ([Ca]i ) and modulation of adenylyl cyclase were measured in addition to NADA effects on CB1 receptor trafficking. Key Results: At concentrations up to 30 μM, NADA failed to activate any signalling pathways via CB1 receptors, with the exception of mobilization of [Ca]i . The elevations of [Ca]i were insensitive to pertussis toxin, and reduced or abolished by blockers of Gq /11 ‐dependent processes including U73122, thapsigargin and a peptide antagonist of Gq /11 activation. Prolonged NADA incubation produced modest loss of cell surface CB1 receptors. The prototypical cannabinoid agonist CP55940 signalled as expected in all assays. Conclusions and Implications: NADA is an ineffective agonist at most canonical cannabinoid receptor signalling pathways, but did promote mobilization of [Ca]i via Gq ‐dependent processes and some CB1 receptor trafficking. This signalling profile is distinct from that of any known cannabinoid, and suggests that NADA may have a unique spectrum of effects in vivo . Our results also indicate that it may be possible to identify highly biased CB1 receptor ligands displaying a subset of the pharmacological or therapeutic effects usually attributed to CB1 ligands.